A novel prognostic model based on four circulating miRNA in diffuse large B‐cell lymphoma: implications for the roles of MDSC and Th17 cells in lymphoma progression. Issue 1 (9th November 2020) - Sun, Rui; Zheng, Zhong; Wang, Li; Cheng, Shu; Shi, Qing; Qu, Bin; Fu, Di; Leboeuf, Christophe; Zhao, Yan; Ye, Jing; Janin, Anne; Zhao, Wei‐Li
Abstract : MicroRNA (miRNA) have been emerged as prognostic biomarkers in diffuse large B‐cell lymphoma (DLBCL). To understand the potential underlying mechanisms and translate these findings into clinical prediction on lymphoma progression, large patient cohorts should be evaluated. Here, using miRNA PCR array, we analyzed the miRNA expression profiles in serum samples of 20 DLBCL patients at diagnosis, remission and relapse. Four candidate miRNA were identified and subsequently evaluated for their ability to predict relapse and survival. A prognostic model based on four circulating miRNA (miR21, miR130b, miR155 and miR28) was established and tested in a training cohort of 279 patients and in a validation cohort of 225 patients (NCT01852435). The prognostic value of the 4‐circulating miRNA model was assessed by univariate and multivariate analyses. The novel 4‐circulating miRNA prognostic model significantly predicted clinical outcome of DLBCL, independent of International Prognostic Index in the training cohort [hazard ratio (HR) = 2.83, 95% CI 2.14–3.51, P < 0.001] and in the validation cohort (HR = 2.71, 95% CI 1.91–3.50, P < 0.001). Moreover, DNA‐ and RNA‐sequencing was performed on tumor samples to detect genetic mutations and signaling pathway dysregulation. DNA‐sequencing data showed no significant difference of tumor mutation burden between the low‐risk and the high‐risk groups of the 4‐circulating miRNA model. RNA‐sequencing revealed a correlation between the 4‐circulating miRNA model and aberrant Ras protein signaling transduction. The impact of the miRNA signature on oncogenic signaling and tumor microenvironment was analyzed in vitro and in vivo . In B‐lymphoma cells, modulation of the miRNA regulated IGF1 and JUN expression, thereby altering MDSC and Th17 cells. In DLBCL patients, the high‐risk group presented Ras signaling activation, increased MDSC and Th17 cells, and immunosuppressive status compared with the low‐risk group. In conclusion, the easy‐to‐use 4‐circulating miRNA prognostic model effectively predicted relapse and survival in DLBCL. Moreover, the tumor microenvironment contributes to the role of the 4‐circulating miRNA model in DLBCL progression. Abstract : A novel prognostic model based on four circulating miRNA (miR21, miR155, miR130 and miR28) showed independent prognostic significance in diffuse large B‐cell lymphoma. The 4‐circulating miRNA signature correlated with aberrant Ras protein signal transduction via IGF1 and JUN expression, and MDSC‐ and Th17 cell‐dependent lymphoma progression.